Aminodecalone Scaffolds – Enantioselective Synthesis, Indole and Quinoline Annulation. Issue 32 (17th August 2018) - Schäfer, Benjamin; Schmidtmann, Marc; Christoffers, Jens
Abstract : Optically active benzo[ b ]carbazole and benzo[ b ]acridine derivatives were prepared by Fischer indole or Friedländer quinoline annulation from 2‐oxodecalone‐4a‐carboxylates with a quaternary stereocenter. As an additional point for diversification, the target compounds carry a nitro function, which was transformed to an amide or lactam after reduction. The scaffold itself was accessed by asymmetric, copper catalyzed Michael reaction of a β‐oxoester with methyl vinyl ketone utilizingl ‐valine diethyl amide as chiral auxiliary. Two enantiopure, epimeric compounds were obtained with 99 % ee and 92 % ee, which were separated and in parallel sequences submitted to intramolecular aldol reaction and catalytic hydrogenation furnishing the 2‐oxodecalone scaffolds. As a precursor for the primary amino group, the scaffolds contained a nitro function at their 6‐positions, which was reduced at the end of the synthetic sequence. The relative and absolute configurations of all three stereocenters were established by X‐ray crystallography. Abstract : l ‐Valine diethyl amide is the chiral auxiliary of choice to prepare optically active aminodecalone scaffolds with quaternary stereocenter by enantioselective copper‐catalyzed Michael reaction followed by Robinson annulation. Intermediate products were further submitted to Fischer indole and Friedländer quinoline annulation.